A Literature Review of "Kaarudak kulikai" in the treatment of Cobra venom (Nalla Paampu) in Siddha Medicine - Nithiakumar, N.; Nushrath Roshana, M. (Government Siddha Medical College And Hospital, Palayamkottai, 2024)
Background: Siddha Toxicology is important part is dealt with Plant, Minerals and Animal poisons. Snake venom is important part in Animal poison. Sixty four types of poisonous snakes mentioned in Siddha texts. In these; cobra venom (Naja naja) is most dangerous in all over the world. Snake bite is a neglected public health issue in tropical and subtropical countries. About 5.4 million snakebite occur each year, resulting in 1.8 to 2.7 million cases of envenoming. There are between 81410 and 137880 deaths and around three times as many amputations and other permanent disabilities each year. Originality / Value: Cobra venom has been considered as difficult to treat due to miss diagnosis and severity in nature. With these ideas when we searched in the Siddha Literatures we found "Kaarudak Kulikar' for cobra venom. It is mentioned in the book "Gunapadam Thaathu Jeeva Vahuppu" page no 589,590. Objective: The aim of this study was to literature related review the important characters of "Kaarudak Kulikai" which is in the treatment for Cobra venom. Methodology: Data were collected from the authenticated text books and studies in details according to their properties related to Siddha aspect. Collected data had been analyzed according to the organoleptic characters and pharmacological action which enables the Kulikai to act on Cobra venom. Findings: The results showed that, twelve ingredients were used and 9(75%) are plant and 3(25%) are thaathujeevam. These ingredients contain siddha properties (bitter5 (35.71%); sweet and sour taste 4 (28.57%)}; cold potency 56.25% (09) and pungent efficacy 58.33% (07)); pharmacological actions (diuretic 14.28% (06), antidote, laxative, anti-inflammatory and carminative 11.9% (05), anodyne and diaphoretic 9.52% (04) respectively Conclusions: It is that all the ingredients of the Kulikai have the property and the pharmacological action to cure for cobra venom. Therefore Kaarudak Kulikai is the best healer for Cobra venom. Although this review can be provide useful documentation for the management of Cobra venom in Siddha Medicine, further extensive scientific studies should be carried out in future.
Keywords: Siddha